Cu2O-Cu double-site nanometer material rich in grain boundary as well as preparation method and application of Cu2O-Cu double-site nanometer material

By preparing Cu2O-Cu two-site nanomaterials rich in grain boundaries, the problem that Cu+ sites cannot be stable for a long time is solved, the selectivity and Faraday efficiency of C2+ products are improved, the occurrence of side reactions is reduced, and the CO2RR process is optimized.

CN119506939AActive Publication Date: 2025-02-25EAST CHINA UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411694030.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-25
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The existing oxide-derived copper-based catalysts cannot exist stably for a long time during the CO2RR process, resulting in low selectivity of C2+ products and serious side reactions of hydrogen evolution and monocarbon, hindering the development of catalysts in industrial applications.

Method used

A method of preparing Cu2O-Cu two-site nanomaterial rich in grain boundaries is adopted. A wet gel is formed by mixing and reacting the copper salt solution with propylene oxide solution. Then, a gelled copper-based hydroxychloride precursor is obtained under the extraction of acetone. After annealing and insulated with H2/Ar mixed gas, a Cu2O-Cu phase interface is formed. Finally, a large number of grain boundaries are formed through electrochemical pre-reduction process to stabilize Cu+ sites.

Benefits of technology

The long-term retention of Cu+ sites is achieved, the selectivity of C2+ products is improved, the side reactions of hydrogen evolution and monocarbon are reduced, the adsorption and activation of CO2 are promoted, and CO is preferred, which is conducive to C-C coupling, thereby improving the Faraday efficiency of C2+ products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506939A_ABST
    Figure CN119506939A_ABST
Patent Text Reader

Abstract

The invention discloses a Cu2O-Cu double-site nanometer material rich in grain boundaries and a preparation method and application thereof.The method comprises the following steps that a copper salt solution and an epoxypropane solution are mixed and react to form wet gel, a gel-state copper-based hydroxyl chloride precursor is obtained under the extraction action of acetone, then the precursor is annealed in air, and the Cu2O-Cu double-site nanometer material rich in the grain boundaries is obtained. And carrying out heat preservation in H2 / Ar mixed gas to form a large number of Cu2O-Cu phase interfaces, and forming a large number of grain boundaries in an electrochemical pre-reduction process to obtain the Cu2O-Cu double-site nano material rich in the grain boundaries. The grain size of the Cu2O-Cu double-site nanometer material rich in the grain boundary can range from 200 nm to 300 nm, and the surface of the Cu2O-Cu double-site nanometer material rich in the grain boundary contains a large number of phase interfaces and grain boundaries. The nanometer material rich in the crystal boundary Cu2O-Cu double sites can be applied to electrocatalytic carbon dioxide reduction reaction, has high multi-carbon product selectivity, and has a certain effect of inhibiting CO by-products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical functional materials, and in particular to a Cu2O-Cu dual-site nanomaterial rich in grain boundaries, a preparation method and an application thereof. Background Art

[0002] The accumulation of greenhouse gas CO2 in the atmosphere is the main driving factor for a series of global environmental problems such as climate change and greenhouse effect. How to effectively reduce excessive carbon dioxide emissions and redevelop and utilize excess carbon dioxide has become a key issue of common concern to the international community. The electrochemical CO2 reduction reaction (CO2RR) uses renewable clean energy to convert CO2 into high-value-added chemicals and fuels, and has the potential to achieve carbon cycle and store renewable energy. The production of multi-carbon (C 2+ ) products (such as ethylene (C2H4), ethanol (C2H5OH), and n-propanol (C3H7OH)) are particularly desirable in practical applications. Copper-based catalysts have good application prospects in the production of multi-carbon products due to their moderate *CO adsorption energy.

[0003] Although Cu in oxide-derived copper (OD-Cu) + The presence of can make copper-based catalysts have higher C 2+ Product activity and selectivity, but Cu + The inability to maintain long-term stability during the CO2RR process remains a problem that needs to be solved. 2+ The products are often produced at higher potentials, and hydrogen evolution and single carbon side reactions are serious, which is not conducive to C 2+ The formation of products. + Problems such as the inability to survive for a long time in the CO2RR process have seriously hindered the OD-Cu catalyst from utilizing synergistic effects to produce C in the CO2RR process. 2+ Industrial application of products and development of this type of catalyst.

[0004] Therefore, it is necessary to develop a preparation method that is economical, environmentally friendly, and can make Cu + It is retained for a long time during the reaction and has a higher C 2+ Product-selective CO2RR Cu2O-Cu dual-site nanocatalysts are urgently needed. Summary of the invention

[0005] The purpose of the present invention is to provide a Cu2O-Cu dual-site nanomaterial rich in grain boundaries and a preparation method and application thereof, which overcomes the problem that existing oxide-derived copper-based catalysts catalyze CO2RR to obtain C 2+ The product selectivity is not high, hydrogen evolution and single carbon side reactions are serious, and Cu+ The problem of sites not being able to be retained efficiently.

[0006] In one aspect of the present invention, the present invention proposes a method for preparing a Cu2O-Cu dual-site nanomaterial rich in grain boundaries. According to an embodiment of the present invention, the method comprises the following steps: mixing a copper salt solution with a propylene oxide solution to form a wet gel, obtaining a gel-state copper-based hydroxychloride precursor under the extraction of acetone, then annealing the gel-state copper-based hydroxychloride precursor in air, and keeping it warm in a H2 / Ar mixed gas to form a large number of Cu2O-Cu phase interfaces, and finally forming a large number of grain boundaries in the obtained catalyst through an electrochemical pre-reduction process, thereby obtaining the Cu2O-Cu dual-site nanomaterial rich in grain boundaries.

[0007] In addition, the method for preparing a grain boundary-rich Cu2O-Cu dual-site nanomaterial according to the above embodiment of the present invention may also have the following additional technical features:

[0008] In some embodiments of the present invention, the solvent of the propylene oxide solution is a mixture of anhydrous ethanol and deionized water, and the volume fraction of propylene oxide in the propylene oxide solution is 2% to 10%.

[0009] In some embodiments of the present invention, the copper salt is copper chloride, the solvent of the copper salt solution is deionized water or anhydrous ethanol, and the concentration of the copper salt solution is 0.5 to 2 mol / L, preferably 1 to 1.5 mol / L.

[0010] In some embodiments of the present invention, washing and drying are performed after the mixed reaction is completed, the solvent used for washing is acetone, the drying temperature is 50-80°C, and the drying time is 2-12 hours, such as 2 hours, 4 hours, and 8 hours. The washing process also includes a centrifugal operation, with a rotation speed of 6000-10000 rpm, preferably 7500-8500 rpm, such as 7500 rpm, 8000 rpm or 8500 rpm.

[0011] In some embodiments of the present invention, the gelled copper-based hydroxychloride precursor is annealed in air at a temperature of 300-500° C., such as 400° C., and the annealing time is 120-240 min, preferably 120-180 min.

[0012] In some embodiments of the present invention, the insulation temperature in the H2 / Ar mixed gas is 200-400°C, preferably 250-300°C, and the insulation time is 60-480 min, preferably 90-150 min.

[0013] In some embodiments of the present invention, the current density of the electrochemical pre-reduction process is 50-150 mA·cm -2 , for example 100mA·cm -2 The time of the electrochemical pre-reduction process is 120 to 180 seconds, for example 120 seconds.

[0014] In another aspect of the present invention, the present invention provides a Cu2O-Cu dual-site nanomaterial rich in grain boundaries. According to an embodiment of the present invention, the Cu2O-Cu dual-site nanomaterial rich in grain boundaries is prepared by the preparation method of the Cu2O-Cu dual-site nanomaterial rich in grain boundaries.

[0015] In addition, the grain boundary-rich Cu2O-Cu dual-site nanomaterial according to the above embodiment of the present invention may also have the following additional technical features:

[0016] In some embodiments of the present invention, the Cu2O-Cu dual-site nanomaterial rich in grain boundaries is a spherical nanoparticle. The particle size of the Cu2O-Cu dual-site nanomaterial rich in grain boundaries may be 200-300 nm.

[0017] In another aspect of the present invention, the present invention proposes an application of the grain boundary-rich Cu2O-Cu dual-site nanomaterial as a catalyst in a carbon dioxide electroreduction reaction.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] (1) The preparation method of the present invention is rich in grain boundary Cu2O-Cu dual site nanomaterials. Under room temperature, a propylene oxide solution with a certain volume fraction is reacted with a copper salt solution to form a sol-gel, followed by a two-stage heat treatment to form a rich Cu2O-Cu phase interface, and finally a short electrochemical pre-reduction process is used to generate a grain boundary so as to stabilize the Cu + This process is simple, mild, green and environmentally friendly, and easy to achieve large-scale production.

[0020] (2) The grain boundary-rich Cu2O-Cu dual-site nanomaterial of the present invention can be nanoscale spherical particles with uniform particle size, and the particle size range can be 200 to 300 nm.

[0021] (3) When the grain boundary-rich Cu2O-Cu dual-site nanomaterial of the present invention is applied to the CO2RR reaction, it can promote the adsorption and activation of CO2, preferentially adsorb CO, and facilitate CC coupling, thereby increasing C 2+ The selectivity of the product, while the grain boundary can also stabilize Cu + and Cu 0 Double site.

[0022] (4) In a preferred embodiment of the present invention, the Cu2O-Cu dual-site nanomaterial rich in grain boundaries is applied to the C 2+ Product Faraday efficiency FE C2+ The maximum efficiency can reach 75.11%. At the same time, the generation of CH4 by-products is completely suppressed, and the generation of CO by-products is suppressed to a certain extent. The Faraday efficiency of the generated CO is FEco, which can reach a minimum of 9.61%. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a scanning electron microscope (SEM) image of the grain boundary-rich Cu2O-Cu dual-site nanomaterial of Example 1 of the present invention;

[0024] Figure 2 This is a scanning electron microscope (SEM) image of the Cu2O nanomaterial without grain boundaries in Comparative Example 1 of the present invention;

[0025] Figure 3 This is a high resolution transmission electron microscopy (HRTEM) image of the grain boundary-rich Cu2O-Cu dual-site nanomaterial of Example 1 of the present invention;

[0026] Figure 4 This is a high-resolution transmission electron microscopy (HRTEM) image of the Cu2O nanomaterial without grain boundaries in Comparative Example 1 of the present invention;

[0027] Figure 5 This is an X-ray diffraction (XRD) diagram of the grain boundary-rich Cu2O-Cu dual-site nanomaterial of Example 1 of the present invention;

[0028] Figure 6 This is an X-ray photoelectron spectrum (XPS) of the grain boundary-rich Cu2O-Cu dual-site nanomaterial of Example 1 of the present invention, wherein: Figure 6 (a) is the electronic energy spectrum of Cu 2P. Figure 6 (b) is the Cu LMM Auger electron spectrum;

[0029] Figure 7 In-situ X-ray diffraction (XRD) patterns of the Cu2O-Cu dual-site nanomaterials rich in grain boundaries and the Cu2O nanomaterials without grain boundaries of Example 1(a) of the present invention and Comparative Example 1(b);

[0030] Figure 8 The in-situ Raman images of the grain boundary-rich Cu2O-Cu dual-site nanomaterial and the grain boundary-free Cu2O nanomaterial of Example 1(a) and Comparative Example 1(b) of the present invention;

[0031] Fig. 9This is a Faraday efficiency diagram of the electrocatalytic generation of multi-carbon products from carbon dioxide at different current densities by the Cu2O-Cu dual-site nanomaterials rich in grain boundaries of Example 1 and Example 8 of the present invention and the Cu2O nanomaterials without grain boundaries of Comparative Example 1;

[0032] Fig.10 A ratio diagram of the Faraday efficiency of electrocatalyzing carbon dioxide to generate multi-carbon products and the Faraday efficiency of single-carbon products under different current densities for the grain boundary-rich Cu2O-Cu dual-site nanomaterials of Example 1 and Example 8 of the present invention and the grain boundary-free Cu2O nanomaterial of Comparative Example 1;

[0033] Fig.11 This is a Faraday efficiency diagram of the electrocatalytic production of CO by-product from carbon dioxide at different current densities for the grain boundary-rich Cu2O-Cu dual-site nanomaterials of Example 1 and Example 8 of the present invention and the grain boundary-free Cu2O nanomaterial of Comparative Example 1. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Example 1

[0036] A method for preparing a grain boundary-rich Cu2O-Cu dual-site nanomaterial comprises the following steps:

[0037] (1) 5 mL of propylene oxide, 10 mL of anhydrous ethanol and 0.9 mL of deionized water were fully mixed to form a propylene oxide solution, which was then stored in an ice water bath. The volume of the mixed solution was 15.9 mL.

[0038] (2) Add 2 mL of 1 mol / L copper chloride dihydrate aqueous solution (i.e., CuCl2·2H2O) to 2 mL of anhydrous ethanol, and then add 3 mL of the prepared propylene oxide solution. After the addition is completed, let it stand for 24 hours to promote the formation of the network to obtain a wet gel. After aging, add 8 mL of acetone and let it stand for 72 hours to achieve the extraction effect. Then, centrifuge the obtained gel to separate the precursor for subsequent direct use. Wash the solid product with acetone for 3 times, the centrifugal speed is 8000 rpm, and the centrifugal time is 5 minutes. The washed solid product is dried at normal pressure to obtain a gel-state copper-based hydroxychloride precursor, the drying time is 2 hours, and the drying temperature is 60°C.

[0039] (3) 50 mg of the gel copper-based hydroxychloride precursor was placed in a porcelain boat, placed in a muffle furnace and annealed at 400°C in air for 120 min. After cooling naturally, the boat was placed in a tubular furnace in a H2 / Ar mixed gas and kept at 250°C for 120 min.

[0040] (4) Finally, the working electrode was charged at 100 mA cm -2 The Cu2O-Cu dual-site nanomaterials rich in grain boundaries were obtained by electrochemical pre-reduction for 120 s at a current of .

[0041] The product obtained in Example 1 was characterized by XRD using a D8ADVANCE (Bruker) X-ray diffractometer. Figure 5 As shown. Figure 5 It can be seen that the main diffraction peaks correspond to the (111), (200) and (220) crystal planes of Cu2O (JCPDS 99-0041) and the (111), (200) and (220) crystal planes of Cu (JCPDS 99-0034), proving that the product obtained in Example 1 is Cu2O-Cu dual-site nanocrystals.

[0042] The product obtained in Example 1 was characterized by X-ray photoelectron spectroscopy (XPS) using Thermo Scientific ESCALAB 250Xi. Figure 6 As shown. Figure 6 The electron energy spectrum of Cu 2P in (a) shows that Cu2O (Cu + ) or Cu(Cu 0 ) is characterized by Figure 6 (b) Cu LMM Auger electron spectroscopy (AES) shows that the Cu element in the product is mainly in the monovalent oxidation state (Cu at 916.2 eV). + characteristic peak) and zero valence state (Cu at 918.3 eV 0 characteristic peak).

[0043] Example 2

[0044] A method for preparing a grain boundary-rich Cu2O-Cu dual-site nanomaterial. The difference between this embodiment and embodiment 1 is only that the H2 / Ar mixed gas insulation temperature of 250°C in embodiment 1 is replaced with 300°C, and the remaining steps and conditions are the same as those in embodiment 1.

[0045] Example 3

[0046] A method for preparing a grain boundary-rich Cu2O-Cu dual-site nanomaterial. The difference between this embodiment and embodiment 1 is only that the H2 / Ar mixed gas insulation temperature of 250°C in embodiment 1 is replaced with 400°C, and the remaining steps and conditions are the same as those in embodiment 1.

[0047] Example 4

[0048] A method for preparing a grain boundary-rich Cu2O-Cu dual-site nanomaterial. The difference between this embodiment and embodiment 1 is only that the H2 / Ar mixed gas insulation time of 120 min in embodiment 1 is replaced by 60 min, and the remaining steps and conditions are the same as those in embodiment 1.

[0049] Example 5

[0050] A method for preparing a grain boundary-rich Cu2O-Cu dual-site nanomaterial. The difference between this embodiment and embodiment 1 is only that the H2 / Ar mixed gas insulation time of 120 min in embodiment 1 is replaced by 90 min, and the remaining steps and conditions are the same as those in embodiment 1.

[0051] Example 6

[0052] A method for preparing a grain boundary-rich Cu2O-Cu dual-site nanomaterial. The difference between this embodiment and embodiment 1 is only that the H2 / Ar mixed gas insulation time of 120 min in embodiment 1 is replaced by 180 min, and the remaining steps and conditions are the same as those in embodiment 1.

[0053] Example 7

[0054] A method for preparing a grain boundary-rich Cu2O-Cu dual-site nanomaterial. The difference between this embodiment and embodiment 1 is only that the H2 / Ar mixed gas insulation time of 120 min in embodiment 1 is replaced by 300 min, and the remaining steps and conditions are the same as those in embodiment 1.

[0055] Example 8

[0056] A method for preparing a grain boundary-rich Cu2O-Cu dual-site nanomaterial. The difference between this embodiment and embodiment 1 is only that the H2 / Ar mixed gas insulation time of 120 min in embodiment 1 is replaced by 420 min, and the remaining steps and conditions are the same as those in embodiment 1.

[0057] Example 9

[0058] A method for preparing a grain boundary-rich Cu2O-Cu dual-site nanomaterial. The difference between this embodiment and embodiment 1 is that the electrochemical pre-reduction current density in embodiment 1 is 100 mA·cm -2 Replaced with 50mA·cm -2, the remaining steps and conditions are the same as in Example 1.

[0059] Example 10

[0060] A method for preparing a grain boundary-rich Cu2O-Cu dual-site nanomaterial. The difference between this embodiment and embodiment 1 is only that the electrochemical pre-reduction time of 120s in embodiment 1 is replaced by 180s, and the remaining steps and conditions are the same as those in embodiment 1.

[0061] Comparative Example 1

[0062] The preparation method of a Cu2O nano material without grain boundaries comprises the following steps: preparing 50 mL of 0.02 mol / L copper acetate monohydrate solution (i.e., Cu(CH3COO)2·H2O) in a 100 mL beaker, wherein the solvent is tetraethylene glycol; placing the beaker in an oven at 150° C. for 2.5 hours, washing a solid product three times with isopropanol, the centrifugal speed is 4000 rpm, the centrifugal time is 5 minutes, and drying the washed solid product at 70° C. under normal pressure for 12 hours to obtain a Cu2O nano material without grain boundaries.

[0063] The S-4800 instrument was used to perform SEM micromorphology characterization on the products obtained in Example 1 and Comparative Example 1. The results are as follows: Figure 1 and Figure 2 As shown. Figure 1 It can be seen that the particle size of the product prepared by Example 1 is between 200 and 300 nm, while Figure 2 It can be seen that the product particles prepared by Comparative Example 1 are substantially the same as the particles prepared by Example 1, thus eliminating the influence of catalyst morphology on catalyst performance.

[0064] The products obtained in Example 1 and Comparative Example 1 were characterized by TEM microstructure using Talos F200X instrument. The results are as follows: Figure 3 and Figure 4 As shown. Figure 3 It can be seen that the product prepared by Example 1 has abundant Cu2O and Cu phase interfaces and a large number of grain boundaries. Figure 4 It can be seen that the product prepared by Comparative Example 1 does not have phase interface and grain boundary.

[0065] The products obtained in Example 1 and Comparative Example 1 were subjected to in-situ Raman and in-situ XRD tests. Figure 7 and Figure 8 shown. Figure 7 (a) shows the Cu content of the product of Example 1 + The site disappeared after 2400s of in-situ XRD testing, while Figure 7 (b) shows the Cu content of the product of Comparative Example 1.+ The site completely disappeared after 1200s; Figure 8 (a) shows the Cu in Example 1 + The sites were still retained after 1800s of in-situ Raman testing, and Figure 8 (b) shows the Cu content of the product of Comparative Example 1. + The sites completely disappeared after 840s, proving that the grain boundaries in the Cu2O-Cu dual-site nanomaterials rich in grain boundaries prepared in Example 1 can effectively retain Cu in the CO2RR process. + , to prevent it from being rapidly oxidized.

[0066] Application Examples

[0067] Electrocatalytic CO2 reduction (CO2RR) performance test based on electrocatalytic test system. The test was carried out in a standard three-electrode system using an Autolab 302N electrochemical workstation. The grain boundary-rich Cu2O-Cu dual-site nanomaterials prepared in Examples 1 to 10 were used as working electrodes for the CO2RR reaction. Ag / AgCl was used as the reference electrode and Ni foam was used as the counter electrode (geometric area of ​​0.8×1.7 cm 2 ), using a flow cell electrolytic cell for reaction. The cathode chamber and the anode chamber of the electrolytic cell are separated by an anion exchange membrane, and the electrolytes in the anode chamber and the cathode chamber are 1.0 mol / L potassium bicarbonate solution respectively.

[0068] The gaseous products produced by catalytic CO2RR were quantitatively analyzed using an online gas chromatography system (Shanghai Ruimin, GC-2020) equipped with a FID detector. 1 H NMR) was used to sample and analyze the liquid product in the electrolyte after CO2 electrolysis reduction, and the spectrum was collected on a Bruker AM 400 spectrometer using dimethyl sulfoxide (DMSO) as the internal standard. Example 1, Example 8 and Comparative Example 1 were tested six times respectively, and the current density of the six tests was -250 mA / cm 2 、-300mA / cm 2 、-350mA / cm 2 、-400mA / cm 2 、-450mA / cm 2 and -500mA / cm 2 The test time (i.e., potential holding time) is 10 minutes.

[0069] According to the above method, the products obtained in Example 1, Example 8 and Comparative Example 1 were used as catalysts to carry out CO2RR tests at six current densities to obtain C 2+ The product Faraday efficiency is Fig. 9 As shown, C 2+ Compared with the amount of C1 product Fig.10 shown.

[0070] Depend on Fig. 9 It can be seen that under the best test conditions, i.e. -400mA / cm 2 Under the current density, the Cu2O nanomaterial prepared in Example 1 catalyzes the CO2RR reaction. 2+ The product Faraday efficiency can reach up to 75.11%. Fig.10 It can be seen that the catalyst C prepared in Example 1 2+ The ratio of the product amount to C1 can reach up to 7, which is much higher than that of the catalyst in Comparative Example 1. Fig.11 It can be seen that the catalyst prepared in Example 1 has a certain effect of inhibiting the production of CO by-products.

[0071] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the present invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a Cu2O-Cu dual-site nanomaterial rich in grain boundaries, characterized in that: The following steps are involved: A copper salt solution and a propylene oxide solution are mixed and reacted to form a wet gel, and a gel copper-based hydroxychloride precursor is obtained under the extraction of acetone. The gel copper-based hydroxychloride precursor is then annealed in air and kept warm in a H2 / Ar mixed gas to form a large number of Cu2O-Cu phase interfaces. Finally, a large number of grain boundaries are formed by electrochemical pre-reduction, so as to obtain the Cu2O-Cu dual-site nanomaterial rich in grain boundaries.

2. The method for preparing a grain boundary-rich Cu2O-Cu dual-site nanomaterial according to claim 1, characterized in that: The solvent of the propylene oxide solution is a mixed solution of anhydrous ethanol and deionized water, and the volume fraction of propylene oxide in the propylene oxide solution is 2% to 10%.

3. The method for preparing a grain boundary-rich Cu2O-Cu dual-site nanomaterial according to claim 1, characterized in that: The copper salt is copper chloride, the solvent of the copper salt solution is deionized water or anhydrous ethanol, and the concentration of the copper salt solution is 0.5-2 mol / L.

4. The method for preparing a Cu2O-Cu dual-site nanomaterial rich in grain boundaries according to claim 1, characterized in that: After the mixed reaction is completed, washing and drying are performed, the solvent used for washing is acetone, the drying temperature is 50 to 80° C., and the drying time is 2 to 12 hours.

5. The method for preparing a grain boundary-rich Cu2O-Cu dual-site nanomaterial according to claim 1, characterized in that: The gelled copper-based hydroxychloride precursor is annealed in air at a temperature of 300 to 500° C. and a annealing time of 120 to 240 minutes.

6. The method for preparing a Cu2O-Cu dual-site nanomaterial rich in grain boundaries according to claim 1, characterized in that: The insulation temperature in the H2 / Ar mixed gas is 200-400°C, and the insulation time is 60-480 minutes.

7. The method for preparing a grain boundary-rich Cu2O-Cu dual-site nanomaterial according to claim 1, characterized in that: The current density of the electrochemical pre-reduction process is 50-150 mA cm -2 The time of the electrochemical pre-reduction process is 120 to 180 seconds.

8. A Cu2O-Cu dual-site nanomaterial rich in grain boundaries, characterized in that: The nanomaterial is prepared by the method for preparing the Cu2O-Cu dual-site nanomaterial rich in grain boundaries as claimed in any one of claims 1 to 7.

9. The Cu2O-Cu dual-site nanomaterial rich in grain boundaries according to claim 8, characterized in that: The Cu2O-Cu dual-site nanomaterial rich in grain boundaries is spherical nanoparticles.

10. Use of the grain boundary-rich Cu2O-Cu dual-site nanomaterial as claimed in claim 8 as a catalyst in carbon dioxide electroreduction reaction.

Citation Information

Patent Citations

  • Monatomic alloying catalyst for synthesizing CO through electrocatalysis of CO2 and preparation method of monatomic alloying catalyst

    CN117026283A